The Effects of Technology on the Writing Process for English Language Learners: Comparing EAL Student Responses to Feedback in Hand Written and Electronic Writing Tasks - Osborne, Carl (2017)
This dissertation describes the findings of an investigation into the effectiveness of both electronically written student work with teacher provided electronic feedback and traditional hand-written work and teacher provided hand-written feedback, and which of these two leads to more improvements on surface and meaning level attributes of EAL students’ written work. Twelve students participated in the study comprising of four written tasks and each task comprised of three drafts. Two of the tasks, and the feedback provided on them, were done with traditional pen and paper; and the other two tasks and their feedback were done electronically on Google Docs. Data was gathered on whether a student responded to a piece of feedback, whether any responses made were correctly altered, and the types of each piece of feedback was coded to gain insight between meaning and surface level changes. A questionnaire on the participants perceptions of electronic work and feedback compared to traditional was also conducted at the end of the study. The results did not show any meaningful difference in how often students respond to the feedback in either medium however they did show that electronic feedback had a slightly higher accuracy of responses than traditional feedback. The results of the questionnaire indicated that students prefer to do written work electronically however more than half of them indicated that they thought traditional hand-written work was better for improving their writing despite this. The questionnaire also uncovered some interesting possible reasons for the higher accuracy of electronic work as directions for future research into this area.